2019
DOI: 10.1016/j.jcz.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

North American Condyloderes (Kinorhyncha: Cyclorhagida: Kentrorhagata): Female dimorphism suggests moulting among adult Condyloderes

Abstract: Two new species of Condyloderes are described, C. rohalorum sp. nov. from the deep-sea off California, and Condyloderes flosfimbriatus sp. nov. from the continental shelf in the northern Gulf of Mexico. Additional species are furthermore reported from the two regions, including Condyloderes kurilensis from the Californian deep-sea, one potentially new species from each of the two regions, and the presence of specimens similar to, and potentially conspecific with, the two new species, i.e., Condyloderes cf. C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…A few years later Neuhaus and Sørensen (2013) reported Campyloderes cf. vanhoeffeni Zelinka (1913) in the Guinea Basin at 5064 m and in the southeastern deep-sea region of Canary Island at depths between 5055 m and 5118 m. Sánchez et al (2014a,b) described three additional species, i.e., Mixtophyes abyssalis Sánchez et al (2014a,b), Cristaphyes nubilis (Sánchez et al, 2014a,b), and Krakenella farinelli (Sánchez et al, 2014a,b), from the Guinea Basin, at depths between 5100-5175 m. The remaining and more recent reports of identified abyssal kinorhynchs are restricted to five areas: (1) abyssal plains, 3100-3300 m, around North Atlantic seamounts, from where Yamasaki et al (2019) describe Echinoderes kaempfae Yamasaki et al, 2019; (2) the East Mediterranean, 675-4403 m, from where Yamasaki et al (2018a) describe Echinoderes pterus Yamasaki et al, 2018a,b; (3) abyssal plains, 3351-5766, in the vicinity of the Kuril-Kamchatka Trench, from where Adrianov and Maiorova (2015 describe Cristaphyes abyssorum (Adrianov and Maiorova, 2015), Condyloderes kurilensis Adrianov and Maiorova (2016), Meristoderes okhotensis Adrianov and Maiorova (2018a), and Parasemnoderes intermedius Adrianov and Maiorova (2018b); (4) the abyssal plains, 3250-3853 m, off the Northwest American continental slope, from where Sørensen et al (2018) describe E. anniae, E. dubiosus, E. hamiltonorum, E. juliae, E. lupherorum, E. hviidarum, E. yamasakii, and Sørensen et al (2018Sørensen et al ( , 2019 report three additional known kinorhynch species, E. cf. unispinosus Yamasaki et al (2018a,b), Fissuroderes higginsi Neuhaus and Blasche (2006), and C. kurilensis; (5) the Clarion-Clipperton Fracture Zone, 4319-5012 m, in the tropical East Pacific, from where Sánchez et al (2019) describe Cephalorhyncha polunga, Echinoderes shenlong, and Meristoderes taro.…”
Section: Introductionmentioning
confidence: 99%
“…A few years later Neuhaus and Sørensen (2013) reported Campyloderes cf. vanhoeffeni Zelinka (1913) in the Guinea Basin at 5064 m and in the southeastern deep-sea region of Canary Island at depths between 5055 m and 5118 m. Sánchez et al (2014a,b) described three additional species, i.e., Mixtophyes abyssalis Sánchez et al (2014a,b), Cristaphyes nubilis (Sánchez et al, 2014a,b), and Krakenella farinelli (Sánchez et al, 2014a,b), from the Guinea Basin, at depths between 5100-5175 m. The remaining and more recent reports of identified abyssal kinorhynchs are restricted to five areas: (1) abyssal plains, 3100-3300 m, around North Atlantic seamounts, from where Yamasaki et al (2019) describe Echinoderes kaempfae Yamasaki et al, 2019; (2) the East Mediterranean, 675-4403 m, from where Yamasaki et al (2018a) describe Echinoderes pterus Yamasaki et al, 2018a,b; (3) abyssal plains, 3351-5766, in the vicinity of the Kuril-Kamchatka Trench, from where Adrianov and Maiorova (2015 describe Cristaphyes abyssorum (Adrianov and Maiorova, 2015), Condyloderes kurilensis Adrianov and Maiorova (2016), Meristoderes okhotensis Adrianov and Maiorova (2018a), and Parasemnoderes intermedius Adrianov and Maiorova (2018b); (4) the abyssal plains, 3250-3853 m, off the Northwest American continental slope, from where Sørensen et al (2018) describe E. anniae, E. dubiosus, E. hamiltonorum, E. juliae, E. lupherorum, E. hviidarum, E. yamasakii, and Sørensen et al (2018Sørensen et al ( , 2019 report three additional known kinorhynch species, E. cf. unispinosus Yamasaki et al (2018a,b), Fissuroderes higginsi Neuhaus and Blasche (2006), and C. kurilensis; (5) the Clarion-Clipperton Fracture Zone, 4319-5012 m, in the tropical East Pacific, from where Sánchez et al (2019) describe Cephalorhyncha polunga, Echinoderes shenlong, and Meristoderes taro.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Kinorhyncha from the deep sea have frequently reported unidentified species, mostly from the Indian, Pacific, and Atlantic Oceans (Neuhaus, 2013;Zeppilli et al, 2018). More recently, studies to the species level have received a strong boost, and up to 45 species have recently been described or reported from this environment (Neuhaus and Blasche, 2006;Sørensen, 2008a;Neuhaus and Sørensen, 2013;Sánchez et al, 2014aSánchez et al, ,b, 2019aAdrianov and Maiorova, 2015, 2016Sørensen, 2018, 2019;Sørensen and Grzelak, 2018;Sørensen et al, , 2019Yamasaki et al, 2018aYamasaki et al, ,b,c, 2019Cepeda et al, 2019a). Of these, some species seem to possess wider ranges of distribution than their congeners from the coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in the Introduction, adult dimorphism has so far been confirmed from a single species or more from the genera Echinoderes, Campyloderes, Centroderes and Condyloderes (Higgins, 1977a;Neuhaus & Sørensen, 2013;Neuhaus et al, 2014;Sørensen et al, 2019), and now also of Sphenoderes. In addition, adult moulting was observed in species of Cateria Gerlach, 1956, Zelinkaderes and Antygomonas (Higgins, 1990;Bauer-Nebelsick, 1996;Neuhaus & Kegel, 2015).…”
Section: How Common Is Adult Dimorphism Among Kinorhynchs?mentioning
confidence: 92%
“…Quite recently, the existence of adult dimorphism was reported from another genus, that is Condyloderes Higgins, 1969. Based on spine dimorphism on segment 10, Sørensen et al (2019) documented the presence of two distinct adult female stages in Condyloderes rohalorum Sørensen et al, 2019 and found indications suggesting that a similar dimorphism could exist in other Condyloderes species as well. In the present study, we present the first evidence for adult dimorphism in yet another kentrorhagid genus.…”
Section: Introductionmentioning
confidence: 99%